Topotecan and Cyclophosphamide in Adults with Relapsed Sarcoma. (10th June 2012) - Blanchette, P.; Hogg, D.; Ferguson, P.; Wunder, J. S.; Swallow, C.; Gladdy, R.; Chung, P.; O'Sullivan, B.; Blackstein, M. E.; Catton, C.; Gupta, A. A.
Abstract : Background. The combination of topotecan and cyclophosphamide (TC) has activity in pediatric patients with recurrent sarcoma, especially Ewing's sarcoma (EWS). We sought to determine the toxicity of and response to TC in adults with recurrent sarcoma. Patients and Methods. Adults treated with TC from 2005 to 2010 were reviewed who received T = topotecan at 0.75 mg/m 2 /day (days 1–5) and C = cyclophosphamide at 250 mg/m 2 /day (days 1–5) every 21 days. Results. Fifteen patients, median age 31 years (range 17.5–56) had nonpleomorphic rhabdomyosarcoma (RMS, n = 6 ), EWS, n = 5, synovial sarcoma (SS, n = 2 ) leiomyosarcoma (LMS, n = 1 ), and desmoplastic small round cell tumour (DSRCT, n = 1 ). Median time to progression was 2.5 months (range 1.6–13.0). Partial responses were seen in 2/6 RMS and 1/2 SS. Stable disease was seen in 2/5 EWS, 1/2 SS and 1 DSRCT. The most common reason for stopping treatment was progressive disease 12/15, (80%). Hematologic toxicity was common; 7 (47%) patients required blood product transfusion, 5 (33%) patients had fever/neutropenia. At median follow-up time of 7.7 months, all but 1 patient had died of disease. Conclusion: TC combination is tolerable but has only modest activity in adults with recurrent sarcoma. Other regimens deserve exploration for this high-risk group of patients